2019
DOI: 10.1016/j.omto.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Sperm-Associated Antigen 6 Gene in the Microtubule Function of Cells and Cancer

Abstract: Accumulated evidence shows that sperm-associated antigen 6 (SPAG6) gene has multiple biological functions. It maintains the normal function of a variety of cells including ciliary/flagellar biogenesis and polarization, neurogenesis, and neuronal migration. Moreover, SPAG6 is found to be critically involved in auditory transduction and the fibroblast life cycle. Furthermore, SPAG6 plays an essential role in immuno-regulation. Notably, SPAG6 has been demonstrated to participate in the occurrence and progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
(205 reference statements)
0
28
0
Order By: Relevance
“…COMMD3 levels are elevated in prostate cancer, and have been demonstrated to upregulate C‐MYC expression, promoting proliferation in prostate cancer models 74 . SPAG6 is a member of the cancer‐testis antigen family primarily involved in regulation of the microtubule system, with secondary roles associated with inhibition of the Akt and p53 pathways 75 . High expression levels of SPAG6 occur in numerous malignancies including myelodysplastic syndrome, and genetic knockdown of SPAG6 inhibits cell proliferation of myeloid leukemia cell lines, but pharmacological inhibitors of SPAG6 are not yet available 76 …”
Section: The Role Of Mllt10 In Mllt10r‐mediated Leukemogenesismentioning
confidence: 99%
“…COMMD3 levels are elevated in prostate cancer, and have been demonstrated to upregulate C‐MYC expression, promoting proliferation in prostate cancer models 74 . SPAG6 is a member of the cancer‐testis antigen family primarily involved in regulation of the microtubule system, with secondary roles associated with inhibition of the Akt and p53 pathways 75 . High expression levels of SPAG6 occur in numerous malignancies including myelodysplastic syndrome, and genetic knockdown of SPAG6 inhibits cell proliferation of myeloid leukemia cell lines, but pharmacological inhibitors of SPAG6 are not yet available 76 …”
Section: The Role Of Mllt10 In Mllt10r‐mediated Leukemogenesismentioning
confidence: 99%
“…7A). The interaction with SPAG6 was particularly intriguing due to a number of phenotypic and functional similarities as CCDC103: mouse Spag6 mutants display ciliary defects and many phenotypic hallmarks of PCD (Sapiro et al ., 2002); Spag6 can promote effective migration of cortical neurons and proliferation and migration of mouse embryonic fibroblasts (Sapiro et al ., 2002; Li, Mukherjee, Wu, Zhang, Maria E Teves, et al ., 2015; Alciaturi et al ., 2019) (Li, et al 2015) (Alciaturi et al ., 2019); Spag6 has increased expression in myeloid leukemia lines (Cooley et al, 2016; Yang et al, 2015; Yin et al, 2018); and Spag6 can promote microtubule stability (Zheng et al ., 2019). To validate these protein-protein interactions, we used the bioluminescent resonance transfer assay (BRET)-based LuTHy system (Trepte et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In light of reports implicating SPAG6 in myeloid proliferation and cell migration (Sapiro et al ., 2002; Jiang et al ., 2019; Zheng et al ., 2019), we interrogated the requirement of Spag6 in zebrafish myeloid cells. RT-PCR from flow-sorted spi1b:EGFP cells showed that zebrafish spag6 is expressed in myeloid cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations